Pelatihan Hidup Sehat Melalui Senam Serta Peningkatan Kesehatan Gigi dan Gusi Untuk Lansia di Wilayah Podomoro City, Jakarta Barat - Trijani Suwandi; Tien Suwartini; Ciptadhi Trioka Binartha; Albert; Fergy Christin Maitimu (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Healthy living training through gymnastics and improving dental and gum health for the elderly in Podomoro city is based on attention to the health and quality of life of the elderly. The dental and gum problems that the elderly suffer from include caries, swollen gums and bleed easily, mobile teeth, teeth lost due to extraction or fall out on their own. Missing teeth in the elderly can have a psychological impact on shame, lack of confidence, tension, loss of appetite, malnutrition, difficulty speaking, having no friends, impaired concentration, and unable to work completely. This Community Service (PkM) collaboration with elderly partners in the 14 Podomoro City area, with a total of 51 participants. This PkM is carried out offline in the form of blood pressure checks, elderly exercise, dental and gum health counseling, training on how to brush your teeth properly, and how to clean dentures properly. The success of the program was evaluated by comparing the pre and post-test scores of 51 participants, and the results showed an increase in the average score from 78.92 in the pre-test to 90.69 in the post-test. The evaluation results indicate that the program successfully increased the participants' knowledge, attitude and behavior towards healthy pattern, maintaining teeth and gum health, and it is expected that participants will disseminate this information to the wider community.